The Effect of Financial Knowledge, Financial Behavior, and Income on Financial Satisfaction of Employees in Production at PT Sarana Karya Utama - Irmaya Tri Hartanti; Anita Handayani (Universitas Muhammadiyah Gresik, 2023)
The background in this research is that the employees in this production section are not able to manage their personal finances, so they experience financial dissatisfaction. Many factors influence financial satisfaction, one of which is income, financial knowledge, and financial behavior. This study aims to examine the effect of financial knowledge, financial behavior, and income on financial satisfaction in production employees at PT Sarana Karya Utama. This research uses quantitative methods. The population in this research is employees of the production department of PT Sarana Karya Utama, totaling 52 people, while taking samples using probability sampling technique. The reason is because taking samples from a population of less than 100 samples studied by researchers are 52 production employees. The analysis technique uses instrument test, classic assumption test, and hypothesis test. For test aids using the Statistical Package For The Social Sciences (SPSS). The results of this study indicate that financial knowledge has an influence on financial satisfaction, financial behavior has an influence on financial satisfaction, income has an influence on financial satisfaction.